The Changing Image of Beethoven: A Study in Mythmaking - Comini, Alessandra (Santa Fe, AZ Sunstone, 2008)
No composer in the history of music has undergone so many makeovers in the portrayal of his facial features or the interpretation of his cultural legacy as Ludwig van Beethoven. The myth began during his lifetime when few verbal or visual portrayals of the composer adhered strictly to his physical appearance; instead his mannerisms, manners, and moods prevailed. Promoted from peevish recluse to Promethean hero, he was pictured early on as a 'genius inspired by inner voices in the presence of nature, with leonine hair writhing wildly in symbolic parallel to the seething turbulence of creativity,' according to the author. In this unique study of the myth-making process across two centuries, Alessandra Comini examines the contradictory imagery of Beethoven in contemporary verbal accounts and in some 200 paintings, prints, sculptures, and monuments. With a witty yet penetrating narrative, she moves through these images to construct a collective image of the composer that reflects the many differing impressions left by devoted 'myth makers' ranging from Wagner, Nietzsche, Berlioz, and Brahms to Rolland, D'Annunzio, and Jenny Lind.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); 20th Century (1901-2000); Composer; Legacy